1999
DOI: 10.1038/sj.onc.1203076
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of BAD phosphorylation at serine 112 by the Ras-mitogen-activated protein kinase pathway

Abstract: The function of the pro-apoptotic molecule BAD is regulated by phosphorylation of two sites, serine-112 (Ser-112) and . Phosphorylation at either site results in loss of the ability of BAD to heterodimerize with the survival proteins BCL-X L or BCL-2. Phosphorylated BAD binds to 14-3-3 and is sequestered in the cytoplasm. It has been shown that phosphorylation of BAD at Ser-136 is mediated by the serine/threonine protein kinase Akt-1/PKB which is downstream of phosphatidylinositol 3-kinase (PI3K). The signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
205
1
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(219 citation statements)
references
References 29 publications
11
205
1
2
Order By: Relevance
“…BAD is inhibited by phosphorylation at three distinct sites ( Figure 2): Ser 112 , catalysed by RSK; Ser 136 , catalysed by PKB and Ser 155 catalysed by PKA. Early studies showed that growth factor-stimulated phosphorylation of Ser 112 was inhibited by MEK inhibitors 34,35 although Ser 136 phosphorylation was inhibited by PI3K inhibitors. 36,37 RSK was subsequently shown to be the kinase responsible for phosphorylation of Ser 112 .…”
Section: Erk1/2-dependent Regulation Of Bh3-only Proteinsmentioning
confidence: 99%
“…BAD is inhibited by phosphorylation at three distinct sites ( Figure 2): Ser 112 , catalysed by RSK; Ser 136 , catalysed by PKB and Ser 155 catalysed by PKA. Early studies showed that growth factor-stimulated phosphorylation of Ser 112 was inhibited by MEK inhibitors 34,35 although Ser 136 phosphorylation was inhibited by PI3K inhibitors. 36,37 RSK was subsequently shown to be the kinase responsible for phosphorylation of Ser 112 .…”
Section: Erk1/2-dependent Regulation Of Bh3-only Proteinsmentioning
confidence: 99%
“…The p53 transcription factor also binds to the PTEN promoter and transactivates PTEN gene expression (Stambolic et al, 2001). Ras connects with the PTEN pathway by activating PI3K and by regulating some of the same targets as PI3K, such as BAD and TSC2 (Zha et al, 1996;Datta et al, 1997;Fang et al, 1999;Ma et al, 2005a;Gupta et al, 2007). In addition, activated Ras leads to a loss of PTEN expression through c-Jun-mediated events (Vasudevan et al, 2007).…”
Section: Pten/pi3k Signaling Perturbations In Cancermentioning
confidence: 99%
“…The involvement of Mek in Raf-induced protection from apoptosis is also supported by the finding that PD98059 also prevents B-Rafmediated suppression of caspase activation 101 and Bad phosphorylation. 98,103 Hence, it would appear that one of the mechanisms by which activated Raf prevents apoptosis is via the activation of Mek.…”
Section: The Ras/raf/mek/erk Signaling Kinase Cascadementioning
confidence: 99%
“…97 Phosphorylation of Bad at either serine 112 or serine 133 induces the interaction of BAD with the 14,3,3 protein. 98 Phosphorylated Bad is unable to interact with certain anti-apoptotic Bcl-2 family members shifting the intracellular environment to one favoring cell survival. A-Raf and Raf-1 are the only Raf kinase family members reported to be localized to the mitochondrial membrane.…”
Section: The Ras/raf/mek/erk Signaling Kinase Cascadementioning
confidence: 99%